Tandem non-polymerizing strategy to higher order acrylamide oligomers; potential intermediates for conformational correlations of poly-N-acrylamides - Kendhale, Amol M.; Rajamohanan, Pattuparampil R.; Sanjayan, Gangadhar J. (New Journal of Chemistry, 2008)
This letter describes an efficient tandem non-polymerization strategy to deliver higher order N-acrylamide oligomers. These oligomers, accessible in an one-pot procedure, are potential intermediates for the correlation of stereochemistry (tacticity) with conformation and hydrogen bonding propensities in poly (oligo) N-acrylamides.